2004
DOI: 10.1002/macp.200400016
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorinated Poly(arylene ether ketone) Prepared by a CaH2‐Mediated Polycondensation Reaction

Abstract: Summary: A new reaction procedure has been developed for the polycondensation of hexafluorobisphenol A (6F‐BPA) with bis(pentafluorophenyl) ketone (BPK) in dimethylacetamide (DMAc). In this reaction, CaH2 has been used as a base to facilitate the formation of the phenolate; an alkali metal fluoride was used as a catalyst. Unlike the conventional polycondensation reactions, this procedure avoided producing water during the reaction, and hence, azeotropic distillation with the assistant of a low‐polar co‐solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…From the experimental results it can be concluded that shorter polymerisation times are preferred because of M w decrease at too high polymerisation times. This M w decrease with reaction time corresponds to a well-known chain scission phenomenon induced by the nucleophilic character of the fluoride ions present in the polymerisation medium [38][39][40][41].…”
Section: Dependence Of Polymerisation Time On Molecular Weight Distrimentioning
confidence: 92%
“…From the experimental results it can be concluded that shorter polymerisation times are preferred because of M w decrease at too high polymerisation times. This M w decrease with reaction time corresponds to a well-known chain scission phenomenon induced by the nucleophilic character of the fluoride ions present in the polymerisation medium [38][39][40][41].…”
Section: Dependence Of Polymerisation Time On Molecular Weight Distrimentioning
confidence: 92%
“…Altogether, the disturbing moieties are covalently incorporated in the PAK chains and cycles (see Supporting Information). Therefore we concluded that use of the common base such as K 2 CO 3 , [24,45] , which is established as a suitable catalyst for nucleophilic aromatic substitution of DFB to produce PEK, PES, and related polymers, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] is not suitable to produce molecularly well defined PAK. MALDI TOF measurements of the crude PAK also revealed defects in the polymer chain when solvents such as dimethyl sulfoxide (DMSO), N-cyclohexyl-2-pyrrolidone, and sulfolane, respectively, are used for the syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…The striking difference of PAK synthesis compared to the syntheses of PEK or PES is due to the fact that K 2 CO 3 base undergoes salt formation with the bisphenol component and carbon dioxide is formed. However, it is also suspected that related imperfections are incorporated in PEK or PES, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] because NMR spectroscopy is not sensitive enough to prove small amounts of fragments derived from solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The GPC results obtained under these conditions are shown in Figure 1. Note that the specimens used to obtain these data were recovered by dropping the reaction solution into a mixture of acidic water/methanol (2:1 v:v) so that both the polymer and low molecular weight cyclic oligomers were collected.…”
Section: Synthesis Of Fppementioning
confidence: 99%